EFEKTIVITAS BANK PERKREDITAN RAKYAT (BPR) DALAM RANGKA MEMBANGUN EKONOMI KERAKYATAN DI DAERAH PEDESAAN - Bagus Qomaruzzaman Ratu Edi; Syamsul Hadi (STIE Mandala Jember, 2012)
Government policy making BPR as direction Rural Bank specializes in serving rural communities by focusing on effectiveness. The effectiveness of BPR principles need to be applied in interacting with rural communities to build social economy. The research goal is, (1) to determine the effectiveness of that principle has been applied by the BPR in order to help drive the economy of rural communities to realize the people's economy(2) to determine prekreditan system implemented by BPR and its relationship with the effectiveness of BPR in order to formulate the direction government policy towards the development of existing BPR became Rural Bank. Analysis method used is scoring analysis and multiple linear regression. Discussion of the results showed, (1) the general existence of BPR in Jember is quite equally effective in building a democratic economy for rural communities. (2 by multiple linear regression analysis showed that all systems simultaneously credits applied BPR real impact on the efforts to build a democratic economy for rural communities.